2014
DOI: 10.3109/03008207.2014.959119
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and expression of type VI collagen and elastic fibers in human rotator cuff tendon tears

Abstract: There is increasing evidence for a progressive extracellular matrix change in rotator cuff disease progression. Directly surrounding the cell is the pericellular matrix, where assembly of matrix aggregates typically occurs making it critical in the response of tendon cells to pathological conditions. Studies in animal models have identified type VI collagen, fibrillin-1 and elastin to be located in the pericellular matrix of tendon and contribute in maintaining the structural and biomechanical integrity of ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 40 publications
5
37
0
Order By: Relevance
“…Regardless of the absence of elastin, the observation that four different elastic fibre components were significantly less abundant in torn tendons, suggests a systematic damage to the fibrillin-rich microfibril niche. This is supported by a previous study, which observed a disturbance to fibrillin-rich elastic fibres in large and massive supraspinatus tears using confocal microscopy [5]. The impairment of this micro-environment, which serves as a repository for growth factors, and in particular TGF- β [35], may also help to explain the disruption of the TGF- β axis in tendinopathy [11].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regardless of the absence of elastin, the observation that four different elastic fibre components were significantly less abundant in torn tendons, suggests a systematic damage to the fibrillin-rich microfibril niche. This is supported by a previous study, which observed a disturbance to fibrillin-rich elastic fibres in large and massive supraspinatus tears using confocal microscopy [5]. The impairment of this micro-environment, which serves as a repository for growth factors, and in particular TGF- β [35], may also help to explain the disruption of the TGF- β axis in tendinopathy [11].…”
Section: Discussionsupporting
confidence: 71%
“…It is known to interact directly with MAFP5 [33, 34], as well as LTBP2, with the latter targeting and sequestering TGF- β to the fibrillin-microfibril niche, as well as binding fibulins [35]. FBLN1 has been shown to co-localise with elastic fibres, but there is little information about its exact role [20, 36] The existence of fibillin-rich microfibrils in tendon has previously been described in fetal calf achilles [33], canine flexor digitorum profundus [37], bovine flexor tendon [3], and in human supraspinatus tendons, where they have been shown to be regularly distributed and in the vicinity of tendon cell arrays [5], with all these studies showing elastin to co-localise with the fibrillin microfibers. It is curious, therefore, in light of the high abundance of fibrillin-1 detected here and the use of elastase digestion as validation, that we did not detect any elastin peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…collagen fibre organisation, needs to be addressed and improved. Changes in elastic fibres during tendon healing have not been studied in detail yet, but initial evidence suggests that there is an increase in fibrillin-1 synthesis accompanied with a small increase in elastin production (Thakkar et al, 2014). How this translates directly to the functional aspects of healed tendons is not clear yet.…”
Section: Composition and Healing Of Tendonsmentioning
confidence: 99%
“…Tendons also contain proteoglycans (PGs, i.e. decorin, fibromodulin, biglycan, lumican, aggrecan) in relatively small quantities, with types and amounts varying according to different species, ages and anatomical locations [11,[19][20][21]. In tendon, PGs have been found to play an important role in facilitating fibrillogenesis, regulating extracellular matrix assembly and modulating cellmatrix interaction [20,[22][23][24].…”
Section: Overview Of Tendon Structure and Compositionmentioning
confidence: 99%